(untitled) (Confluenţe Bibliologice, 2018)
The guide includes the objectives, purpose, achievements, impact and sustainability of the LNSS Project (15.10.2015 - 14.10.2018) within the ERASMUS+ Capacity Building Program in the field of higher education.